[RETRACTED] Perbedaan Kualitas Hidup pada Wanita Lanjut Usia yang Mengikuti Senam Gerak Latih Otak dan Terapi Musik Angklung - Suci Tuty Putri (Journal of Ners and Midwifery, 2017)
This article has been retracted as a result of multiple publications from the article by the relevant author.Â Similar articles can be found at the URL :Â http://jks.fikes.unsoed.ac.id/index.php/jks/article/view/671